PENDAMPINGAN GEMA KREASI OLAH SAMPAH, MARKETPLACE, DAN PERMAINAN TRADISIONAL (GEOMETRI) MASYARAKAT DESA SERUT JEMBER - Erfan Yudianto; Luh Putu Indah Budyawati; Kendid Mahmudi (LP2M Universitas Ibrahimy, 2024)
The Community Service Program in Serut Village is designed to empower the community through culture-based literacy, focusing on waste management, the preservation of traditional games, and the promotion of local products under the GEOMETRI initiative. This program addresses the issues of plastic waste pollution and the low interest in reading among rural communities. The methods employed include training for mothers and school-aged children in creating flower arrangements from waste materials, participating in traditional math-based games, and running a marketplace. The service team provides sewing training and supports children in improving their literacy skills. The outcomes of this program include enhancing the creative skills of the community, reducing waste, and strengthening environmental literacy and awareness. Through the GEOMETRI program, village residents learn how to better manage waste by repurposing unused materials, such as making buckets from waste. Furthermore, the preservation of traditional math-based games helps to foster greater public interest in reading and literacy, ultimately contributing to heightened environmental awareness. The market also allows local products from rural communities to be promoted more widely, creating new sustainable economic opportunities. This program is expected to serve as a model for sustainable community empowerment in other areas.